Subjectivities of Body Dynamics among Gay and Heterosexual Older Adults: Interpretations from Artificial Intelligence - Oliveira Leite, Jamil; Rebustini, Flávio (Estudos Interdisciplinares sobre o Envelhecimento, 2026)
Abstract: The growing use of generative artificial intelligence systems in sensitive topics, such as aging, the body, and sexuality, requires critical analysis of the discourses produced by these tools. This study aimed to analyze how different chatbots describe the bodily dynamics of gay and heterosexual older adults and to examine the extent to which these discourses converge with the scientific literature. This was a qualitative, exploratory, and documentary study, with a textual corpus produced from ten standardized questions applied to the chatbots Copilot, Meta AI, Gemini, ChatGPT, Claude, Sider, and DeepSeek. The material was subjected to Bardin’s thematic content analysis. The results indicated categories related to life experience, aesthetics, intersectionality, support networks, mental health, movement, culture, identity, and relationships. The study concludes that generative AI synthesizes social repertoires about male old age but does not operate as a neutral source.